Applying the theory of planned behavior: Examining how communication, attitudes, social norms, and perceived behavioral control relate to healthy lifestyle intention in Singapore. (15th December 2020) - Banerjee, Snehasish; Ho, Shirley S.
ABSTRACT: This study investigates the extent to which communication variables, namely, interpersonal communication and attention to mass media, as well as the key components in the theory of planned behavior (TPB), including, attitudes, social norms, and perceived behavioral control, are associated with healthy lifestyle intention in Singapore. Healthy lifestyle intention was conceptualized and operationalized in terms of individuals' proclivity for physical activity and healthy diet. Data came from a nationally representative computer-assisted telephone interview (CATI) of 1055 Singaporeans aged 21 years and above. Hierarchical regression analysis was conducted. Results show that both communication and planned behavior variables were positively related to behavioral intention. The study is important for both theory and practice. Theoretically, it demonstrates the possibility to extend the TPB with two more variables: interpersonal communication and attention to mass media. On the practical front, the results inform health authorities and marketers on ways to promote public adoption of healthy lifestyle in Singapore.